2015
DOI: 10.1021/acs.jpca.5b01443
|View full text |Cite
|
Sign up to set email alerts
|

Interaction of Metal Ions with the His13-His14 Sequence Relevant to Alzheimer’s Disease

Abstract: The interaction of a series of metal ions (i.e., groups 1 and 2, first-row transition metals, and groups 11-14) with the His13-His14 sequence relevant to Alzheimer's disease has been studied using quantum chemical calculations. Metal ions prefer to occupy three coordination sites at two Nδ of the imidazole rings and one carbonyl oxygen. Simulated IR spectra reveal that vibrational frequency of C-O stretch affords a sensitive probe for understanding the interaction of His13-His14 with metal ions. The relative s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 75 publications
0
4
0
Order By: Relevance
“…There are a number of different mechanisms through metal ions can aggravate AD [41]. By the interaction of metal ions with peptides, the conformation of peptide suffers some modifications with the formation of peptide-metal complexes with or without aggregation and peptide fibril formation [42].…”
Section: Resultsmentioning
confidence: 99%
“…There are a number of different mechanisms through metal ions can aggravate AD [41]. By the interaction of metal ions with peptides, the conformation of peptide suffers some modifications with the formation of peptide-metal complexes with or without aggregation and peptide fibril formation [42].…”
Section: Resultsmentioning
confidence: 99%
“…96,97 Cu-Aβ model systems that consider copper cation and its coordination sphere have been used to study copper preferences in the Aβ sequence and to propose plausible mechanisms to the reactions that increase oxidative stress. 98,99 Recently, Bertini et al have used density functional theory (DFT) methods to study the mechanism of the O 2 reduction to OH − + •OH radical mediated by Cu-Aβ model systems and ascorbate. 100 As has been pointed out, the use of small model systems has allowed the understanding of copper coordination and reactivity of Cu-Aβ complexes.…”
Section: 1mentioning
confidence: 99%
“…For these reasons, a number of techniques have been employed to determine the amino acids involved in the recognition of metals by Aβ. It is generally accepted that metal ions are bound to the histidine residues at positions 6, 13, and 14 [56]. Several studies have demonstrated that the interaction of Cu 2+ , Zn 2+ , Fe 3+ , and Al 3+ with Aβ is maintained by their coordination with His13-His14 of the peptide.…”
Section: Interaction Of Metals With Amyloid Beta and Hydrogen Peroxidmentioning
confidence: 99%